Efektivitas Konseling Kelompok dengan Analisis Transaksional Untuk Mereduksi Kecemasan Berbicara di Depan Kelas di SMPN 8 Bukittinggi - Eka Nur Septiana; Alfi Rahmi; Rahmawati Wae (Educational Guidance and Counseling Development Journal, 2020)
This study moved from the phenomenon of students experiencing anxiety speaking in front of the class where students were afraid and hesitant to speak in front of the class, afraid of being laughed at, afraid of wrong answers related to what was told by the teacher to the front of the class, the fear and anxiety were indicated by the characteristics physical characteristics seen when students are told to speak in front of the class, such as hands that are trembling and sweating cold, faces that are red and pale and other physical characteristics. To reduce the speaking anxiety, BK teachers try to overcome it through several types of services, one of which is group counseling services. Researchers try to do group counseling services with a transactional analysis approach.This research is classified as a pre experimental research model of One Group Pretest Posttest Design. The population was some VIII grade students totaling 187 people, or sampling that is students who were indicated to have high speaking anxiety based on non random sampling techniques and BK teacher recommendations. The data collection instrument is a Likert scale. Data analysis techniques used Wilcoxon test, while data analysis requirements used normality test, homogeneity test, using Statistical Product and Service Solution (SPSS) version 23. The results of research that have been done there are differences between the pretest value and the posttest value. From the results of statistical tests it is known that the results of asymp sig (2-tailed) obtained values of (0.005), which means smaller than alpha (0.05). So it can be said that Ha is accepted, so it can be said Ha is accepted, it means there is a decrease in speaking anxiety in front of the class for pretest and posttest through group counseling services with transactional analysis.